Biosynthesis of Selenium Nanoparticles utilizing Leaf Extract of Wedelia glauca (Ortega) O. Hoffm Ex Hicken (Asteraceae): Characterization and Evaluation of Anticancer Properties - Shanthamani, M.; Karthik, K.; Krishnavignesh, L.; Srinivasan, Anbalagan (Asian Journal of Chemistry, 2025)
This study focuses on the synthesis and biological evaluation of selenium nanoparticles (SeNPs) derived from the leaf extract of Wedelia glauca (Ortega) O. Hoffm. Ex Hicken (Asteraceae) through a green bioreduction process using sodium selenite. The synthesized nanoparticles were separated from the reaction mixture using high-speed centrifugation and subsequently characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM) and UV-visible spectroscopy. The XRD results revealed that the SeNPs possessed a crystalline structure, with an average particle size of 21.73 nm, corroborated by TEM analysis. The SeNPs demonstrated the ability to activate immune responses against cancer cells, induce mitochondria-mediated apoptosis and exhibit significant anticancer activity both in vitro and in vivo, particularly against prostate malignancies. These findings suggest that SeNPs synthesized via a sustainable method hold considerable promise for biomedical and therapeutic applications.